Molecular and acoustic evidence support the species status of Anthus rubescens rubescens and Anthus [rubescens] japonicus (Passeriformes: Motacillidae) - Doniol-Valcroze, Paul; Coiffard, Paul; Alström, Per; Robb, Magnus; Dufour, Paul; Crochet, Pierre-André (Zootaxa, 2023)
The Buff-bellied Pipit Anthus rubescens comprises two allopatric subspecies groups: A. r. rubescens and A. r. alticola in North America and A. [r.] japonicus in north-east Asia. Despite their great morphological resemblance in breeding plumage, most individuals can be assigned to one or the other subspecies group in non-breeding plumage. Allopatric distributions, morphological differentiation and previously reported molecular divergence suggested the need for additional taxonomic study to assess the rank of these two populations. To resolve the taxonomy of the Buff-bellied Pipit species complex we analysed i) two mitochondrial DNA (mtDNA) loci and ii) nine bioacoustic parameters across 69 sound recordings (338 flight calls) recovered from public databases using principal component analysis and Euclidean distance measures. By comparing our mtDNA and call divergence measures with similar values measured between long-recognised species pairs of the genus, we show that the level of mitochondrial and acoustic divergence between the two Buff-bellied Pipit subspecies groups is typical of species-level divergence in the genus Anthus. Therefore, we recommend splitting the Buff-bellied Pipit species complex into two species: Anthus rubescens (American Pipit) and Anthus japonicus (Siberian Pipit). Our results also suggest that the Water Pipit A. spinoletta deserves taxonomic reassessment as its lineages are highly divergent in acoustics and mtDNA, while mtDNA relationships suggest paraphyly relative to the Rock Pipit A. petrosus. Our work highlights the crucial importance of integrative approaches in taxonomy and the usefulness of bioacoustics in studying cryptic diversity.